Soil Erosion and Controls in the Slope-Gully System of the Loess Plateau of China: A Review - Zhu, Bingbing; Zhou, Zhengchao; Li, Zhanbin (Frontiers in Environmental Science, 2021)
The Loess Plateau has long been suffering from serious soil erosion of which erosion from the slope-gully system now is dominant. Slope-gully system is characterized with distinctive erosion distribution zones consisting of inner and inter gully areas wherein erosion patterns spatially vary, acting as both sediment source and the dominant sediment and water transport mechanism. In this paper, a substantial body of research is reviewed concentrating on the soil erosion processes and control practices in the slope-gully system. Inner gully is identified as the main sediment sources while runoff and sediment from the upland inter gully areas is found to significantly affect down slope erosion processes. Corresponding, the protective vegetation pattern and coverage should be strategically designed for different erosion zones with an emphasis on the critical vegetation cover and pattern to reduce sediment yield of the whole slope-gully system. Check-dam could change the base level of erosion and reduce slope length of gully side, which will further decrease the possibility and magnitude of gravity erosion. We concluded that understanding the erosion processes and implementing erosion practices for the slope-gully system are of importance and require more research efforts that probably emphasizing on: 1) the influence of upland runoff on erosion processes at downslope; 2) the relationship between hydraulic characteristics of overland flow and erosion process at slope-gully system scale; 3) physical mechanisms of different vegetation patterns on slope-gully erosion process.